The Relationship Between God and Humans in an Islamic Perspective - Julhadi, Julhadi; Dahyar, Dahyar; Akhir, Nur Afzan Binti Md (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2024)
In this article, the naming of God as Rabb, Malik and Ilaah, where God himself is something that exists in the human mind. In the human structure, the heart is a small chamber that contains the conscience or inner voice or is a small point or small box that is hidden firmly and neatly in the heart. Conscience is the line between humans and God or what connects humans with God. Meanwhile, Man is a creature chosen by God, as His caliph on earth, as well as a semi-celestial and semi-worldly creature, in whom the qualities of recognizing God, being free, trustworthy, and having a sense of responsibility towards himself and the universe are instilled; as well as the gift of superiority over the universe, heaven and earth, which has expressions as Al-Basyar, Anas, al-insan and Bani Adam. In Islam, God is the creator of humans as well as the universe, but various problems plague this life which only prioritizes material elements, coupled with the problem of the Western mindset which only prioritizes human aspects and material elements and eliminates spiritual elements, for example religion and belief in God. This kind of perspective will deny God's role as creator and ruler because the Almighty in this life is only God, He is the one who created everything in this universe, the best creature that He has created is humans. In this research, we used the library research method by collecting books that share the same theme as the discussion.